2022
DOI: 10.3390/ijerph19127346
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Behaviour and Comparison of GPAQ and Travel Diary Transport-Related Physical Activity in Accra, Ghana

Abstract: There is a lack of data on physical activity (PA), active travel, and the comparison of measurement instruments in low-resource settings. The objective of this paper is to describe PA behaviour and the agreement of walking estimates from the Global Physical Activity Questionnaire (GPAQ) and the travel diary in a low-resource setting. We used a cross-sectional survey design to capture data from the residents of Accra (Ghana) between May 2020 and March 2021. Of the 863 participants aged 15+ years, 65% were femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…This is similar to a Malaysian study by Chu HY and Moy FM (2014), which demonstrates that the participants are most active in the domestic physical activity domain, followed by occupation, transportation and leisure [ 21 ]. This is in contrast with studies from Hungary and Ghana; whereby the highest PA is found in the working domain [ 42 , 43 ]. This similar pattern is also noted in lower income countries, with more activities undertaken at work and for transport [ 44 ].…”
Section: Discussioncontrasting
confidence: 86%
“…This is similar to a Malaysian study by Chu HY and Moy FM (2014), which demonstrates that the participants are most active in the domestic physical activity domain, followed by occupation, transportation and leisure [ 21 ]. This is in contrast with studies from Hungary and Ghana; whereby the highest PA is found in the working domain [ 42 , 43 ]. This similar pattern is also noted in lower income countries, with more activities undertaken at work and for transport [ 44 ].…”
Section: Discussioncontrasting
confidence: 86%
“…The domains of the questionnaire were categorised into socio-demographic characteristics of participants, lifestyle factors, self-reported NCD status, and NCD risk factor assessment. The questionnaires have successfully been used in previous studies in Ghana with good internal and external validity [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%